2013
DOI: 10.1038/cddis.2013.244
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 regulates cell fate during epithelial–mesenchymal transition by upregulating survivin

Abstract: Members of the transforming growth factor beta (TGF-β) superfamily are multifunctional cytokines that regulate several cellular processes, including cell cycle arrest, differentiation, morphogenesis, and apoptosis. TGF-β promotes extracellular matrix production and morphological change. Morphogenetic responses to TGF-β include cell migration and epithelial–mesenchymal transition (EMT), which are critical during embryogenesis, development of fibrotic diseases, and the spreading of advanced carcinomas. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 41 publications
4
56
0
1
Order By: Relevance
“…It is difficult to rationalise the inconsistency between studies; however, the types of cell line, media and extra-and intracellular conditions are among the variables that may contribute to these differences. Concerning the apoptosis mechanism, it was reported that treatment with TGF-β1 may increase survivin, which promotes cell cycle progression and inhibits apoptosis during EMT (31). The results of the present study demonstrated that the active form of caspase-3 was decreased and G2/M phase cells were increased in the TGF-β1-treated and MET/return groups.…”
Section: Discussionsupporting
confidence: 55%
“…It is difficult to rationalise the inconsistency between studies; however, the types of cell line, media and extra-and intracellular conditions are among the variables that may contribute to these differences. Concerning the apoptosis mechanism, it was reported that treatment with TGF-β1 may increase survivin, which promotes cell cycle progression and inhibits apoptosis during EMT (31). The results of the present study demonstrated that the active form of caspase-3 was decreased and G2/M phase cells were increased in the TGF-β1-treated and MET/return groups.…”
Section: Discussionsupporting
confidence: 55%
“…Nevertheless, the molecular mechanism of the concomitant apoptosis and EMT remains to be characterized. In retinal pigment epithelial (RPE) cells, survivin was shown to be involved in the control of the TGF-β-mediated cell cycle state, which is important for the induction of EMT [64]. Strikingly, in TGF-β-induced concomitant apoptosis and EMT, certain molecules, such as PKA and STAT3 [34], NOS/NO [42], AMPK [65], and p38 MAP kinase [66][67][68][69], are required for both events.…”
Section: The Implications Of Tgf-β-induced Concomitant Apoptosis and Emtmentioning
confidence: 99%
“…Additionally, N‐cadherin is upregulated during EMT as E‐cadherin is downregulated, the ‘cadherin switch’ . TGFβ also mediates other properties of EMT cells, such as anti‐apoptosis, whereas in non‐EMT cells, it can have a pro‐apoptotic role . Other pathways involved in EMT involve hypoxia‐inducible factor (HIF), which not only induces Twist and Snail expression, but also positively impacts upon pro‐EMT β‐catenin.…”
Section: Epithelial‐to‐mesenchymal Transition An Important Developmementioning
confidence: 99%